Composition and spectroscopy of olivine xenocrysts from the Hawaiian tholeiitic basalts - A.B. Makeyev; V.P. Lutoev; I.P. Vtorov; N.I. Braynchaninova; A.R. Makavetskas (Учёные записки Казанского университета: Серия Естественные науки)
Tholeiitic basalts of the Hawaiian Mauna Loa and Kīlauea volcanoes (USA) contain olivine xenocrysts with chromespinelide inclusions. Their chemical composition and spectroscopic properties were investigated and compared with olivine of another ultrabasite type. Two olivine varieties with the iron content of 10–12 and 18–21.5 mol% Fa were detected. The composition of chromespinelide corresponds to the following two varieties: subferrialumochromite and subferrisubalumochromite. Mössbauer spectroscopy and EPR of the olivine showed only minor traces of iron oxidation. The composition of chromespinelide is testimony to its high-temperature metamorphism. The typomorphic features of the studied minerals (from the mantle) are close to those of the lherzolite-harzburgite complex of rocks of the Urals alpinotype ultrabasites.